PENGARUH PENGGUNAAN MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KEMAMPUAN MENULIS PUISI KELAS XII SMA NEGERI 2 SIDRAP : The Effect of Using Project-Based Learning Model on The Ability to Write Poetry in Class XII SMA Negeri 2 Sidrap - Iqbal, Muhammad; Sultan; Asri, Aswati (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study is a quantitative research using a pre-experimental method aimed to: (1) describe the poetry writing skills of 12th-grade students at SMA Negeri 2 Sidrap before applying the Project-Based Learning model; (2) describe the students' poetry writing skills after using the model; and (3) examine the significant impact of the Project-Based Learning model on students' poetry writing skills. The sample consisted of 120 students selected randomly from a population of 173 students. Data were collected through pretests and posttests. The analysis results showed a significant improvement in students' poetry writing skills after applying the model, with a t-test result indicating a t-value (17.74) greater than the t-table (1.980), proving that the Project-Based Learning model had a significant effect on students' poetry writing skill.